INVENTIVIDADES DOCENTES EM REDE - Carvalho, Felipe; Santos, Edmea; Pimentel, Mariano; Santos, Rosemary dos; Menezes, Marcos Vinícius Dias de (Revista Docência e Cibercultura, 2022)
Editorial v. 6, n. 5 (2022): DOCÊNCIA EM TEMPOS DE CRISE, EXPERIÊNCIAS E DESAFIOS (EDIÇÃO ESPECIAL)